Text Cohesion vs. Fine-Grained Indices of Syntactic Complexity in L2 Writing: Their Relations to Overall EFL Writing Scores - Zafer Susoy (Van Yüzüncü Yıl Üniversitesi Eğitim Fakültesi Dergisi)
The purpose of this study is to determine how various cohesion indices (CI), as determined by the Tool for the Automatic Analysis of Cohesion (TAACO), and syntactic complexity indices, as determined by the Tool for the Automatic Analysis of Syntactic Sophistication and Complexity (TAASSC), relate to the writing quality evaluations of English as a Foreign Language (EFL) learners. This study employs a quantitative research methodology, using regression and correlation analysis to examine the collected learner corpus. Although there was no noticeable relationship between coherence devices and writing quality, syntactic complexity is a key differentiator between proficient and less proficient EFL writers. Metrics such as clause length, and use of complex nominals per clause contribute to a sophisticated writing style, signaling advanced linguistic capability. Furthermore, 50% of the variance in the overall writing quality scores of the learners was explained by the regression model only when text length (TL) and proficiency level were added as confounding variables. The study's findings are discussed in light of the related literature and future directions.